Objectives for New Error Criteria for Mobile Broadcasting of Streaming Audiovisual Services. (6th July 2008) - Himmanen Himmanen, Heidi Heidi; Hannuksela Hannuksela, Miska M. Miska M.; Kurki Kurki, Teppo Teppo; Isoaho Isoaho, Jouni Jouni
Abstract : This paper demonstrates the need of and objectives for new error criteria for mobile broadcasting and the problems related to defining numerical error criteria for video services. The current error criterion used in digital video broadcasting to handheld (DVB-H), namely, multiprotocol encapsulation forward error correction (MPE-FEC) frame error ratio (MFER) 5%, was defined to enable instantaneous measurements but is not accurate enough for detailed simulations or postprocessing of measured data. To enable accurate transmission system design, parameter optimization, and performance evaluation, it is necessary to define new practical criteria for measuring the impact of transmission errors. The ambiguity of the MFER criterion is studied, and results for other conventional error criteria are derived from transmission system simulations and objective video quality measurements. The outcomes are compared to results from studies on subjective audiovisual quality. Guidelines are given on the next steps of developing new objective criteria for wireless and mobile video. It is suggested that subjective tests are performed based on the average length and average amount of errors derived from verified mobile radio channel models.